Trends in the Mortality and Death of Periviable Preterm Infants in the United States, 2011 to 2020 - Patel, Jenil; Oluwafemi, Omobola; Tang, Tiffany; Sunny, Angel; Parmar, Narendrasinh; Doshi, Harshit; Bhatt, Parth; Donda, Keyur; Messiah, Sarah E.; Dapaah-Siakwan, Fredrick (American Journal of Perinatology, 2024)
This study aimed to examine the trends in the infant mortality rate (IMR) and the trends in the timing of death among periviable preterm infants at 22 to 24 weeks' gestational age (GA) in the United States from 2011 to 2020.Retrospective, serial cross-sectional analysis of periviable preterm infants born in the United States at 22 to 24 weeks' GA using the linked birth/infant death records from the Centers for Disease Control and Prevention. Data were analyzed from 2011 to 2020. The exposure was the year of death, and the outcome was the changes over time in the IMR and the timing of death. Further, we evaluated racial differences in the timing of death. We used nonparametric trend analysis to evaluate changes in mortality rate across the study period.The IMR was inversely related to GA, and for each GA and race/ethnicity, the IMR significantly declined during the study period. The IMR rate was highest in the first 7 days of life for all GAs and races/ethnicities. While Non-Hispanic White infants had a higher infant neonatal mortality rate than non-Hispanic Black infants, non-Hispanic Black infants had a higher postneonatal mortality rate.The IMR among periviable infants born at 22 to 24 weeks' GA improved for all GAs and races in the United States between 2011 and 2020. However, significant racial differences in the timing of death exist.
Keywords: neonatology; periviable newborn; racial/ethnic disparities; mortality; periviable births; trends